Screening test for low bone density using DXA method – causes’ analysis of patients’ participation - Banaś, Tomasz; Klimek, Marek; Skotniczny, Krzysztof; Gruca-Banaś, Lucyna (Reumatologia/Rheumatology, 2005)
Screening tests are due to identify a disease or a defect by methods that can be easily applied on a large scale. It is not an usual diagnostic process and requires further investigation. Aim: The aim of the study was to present the cause of women’s participation in screening test for osteoporosis. Methods: The group of 301 women was investigated. The causes of participation in screening test were analyzed and mean values of BMD T-score were compared according to the reason of taking part in the screening test. The whole population was than stratified into two groups: group A – patients examined for the first time and group B – patients examined for the second or more times. Mean values of BMD T-score were compared in both groups. Conclusions: The most common reason for participating in the screening test was medical recommendation. For 64% of the patients this was the first screening test and 36% of patients have already underwent at least one screening test for osteoporosis. Mean values of BMD T-score ware statistically different dependent on the cause of participation in the screening test. Also group A and group B were characterized by different mean values of BMD T-score.